1997
DOI: 10.1159/000121264
|View full text |Cite
|
Sign up to set email alerts
|

Corpus Callosotomy for Medically Intractable Seizures

Abstract: To identify factors influencing outcome and morbidity in patients selected for corpus callosotomy, we retrospectively reviewed 23 patients with intractable generalized seizures who underwent corpus callosotomy between 1991 and 1994. Three patients had a complete corpus callosotomy, while 20 had an anterior callosotomy. Three of those patients subsequently had completion of the anterior callosotomy. Overall, 41% of patients were nearly or completely free of the seizure types targeted for surgical treatment, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 20 publications
0
22
1
1
Order By: Relevance
“…In contrast, Spencer et al (40) observed that two seizure types, low verbal IQ and diffuse ictal EEG patterns, were more frequent in anterior callosotomy failures, and that total callosotomy was warranted for tonic and tonic-clonic seizures with diffuse EEG paroxysms. Sorensen et al (41) also found that normal MRI predicted good outcome, but they noticed that neither neurologic examination nor EEG had any prognostic value.…”
Section: Effect Of Callosotomy On Various Seizure Typesmentioning
confidence: 99%
“…In contrast, Spencer et al (40) observed that two seizure types, low verbal IQ and diffuse ictal EEG patterns, were more frequent in anterior callosotomy failures, and that total callosotomy was warranted for tonic and tonic-clonic seizures with diffuse EEG paroxysms. Sorensen et al (41) also found that normal MRI predicted good outcome, but they noticed that neither neurologic examination nor EEG had any prognostic value.…”
Section: Effect Of Callosotomy On Various Seizure Typesmentioning
confidence: 99%
“…Permanent neurological deficits due to trauma, infarction, or intracerebral hemorrhage occur in less than 4% of patients [13] . Disconnection syndrome in children aged 12 years and younger was reported in 45% of cases, while 67% of older patients were affected and remained symptomatic longer [14] . Approximately 50-66% of patients experience a 50% reduction in the frequency of seizures, with few becoming seizure free [9,10] .…”
Section: Discussionmentioning
confidence: 98%
“…In addition, callosotomy frequently caused a reduction in seizure frequency and severity rather than the transformation of a generalized seizure to a lateralized or partial one. [10][11][12][13][14] Spencer et al found that new or more intense partial seizures occasionally occurred after callosotomy. They hypothesized that the residual partial seizures could actually be fragments of previous generalized seizures.…”
Section: Discussionmentioning
confidence: 99%